Estimation of PKCδ autophosphorylation in U87 MG glioma cells: combination of experimental, conceptual and numerical approaches. Issue 3 (9th May 2016) - Misuth, Matus; Joniova, Jaroslava; Belej, Dominik; Hrivnak, Stanislav; Horvath, Denis; Huntosova, Veronika
Abstract : Golgi apparatus (GA) is a center for lipid metabolism and the final target of ceramide pathway, which may result in apoptosis. In this work localization of highly hydrophobic hypericin is followed by time‐resolved imaging of NBDC6 (fluorescent ceramide) in U87 MG glioma cells. Decrease of NBDC6 fluorescence lifetimes in cells indicates that hypericin can also follow this pathway. It is known that both, ceramide and hypericin can significantly influence protein kinase C (PKC) activity. Western blotting analysis shows increase of PKCδ autophosphorylation at Ser645 ( p (S645)PKCδ) in glioma cells incubated with 500 nM hypericin and confocal‐fluorescence microscopy distinguishes p (S645)PKCδ localization between GA related compartments and nucleus. Experimental and numerical methods are combined to study p (S645)PKCδ in U87 MG cell line. Image processing based on conceptual qualitative description is combined with numerical treatment via simple exponential saturation model which describes redistribution of p (S645)PKCδ between nucleus and GA related compartments after hypericin administration. These results suggest, that numerical methods can significantly improve quantification of biomacromolecules ( p (S645)PKCδ) directly from the fluorescence images and such obtained outputs are complementary if not equal to typical used methods in biology. Abstract : Golgi apparatus (GA) is a center for lipid metabolism and the final target of ceramide pathway, which may result in apoptosis. In this work localization of highly hydrophobic hypericin is followed by time‐resolved imaging of NBDC6 (fluorescent ceramide) in U87 MG glioma cells. These results suggest that numerical methods can significantly improve quantification of biomacromolecules ( p (S645)PKCδ) directly from the fluorescence images and such obtained outputs are complementary if not equal to typical used methods in biology.